Evaluation of Polyherbal Preparation Containing Aegle marmelos and Saraca asoca Plants for Screening of Urolithiasis Disease - Pooja, Pooja; Mazumder, Avijit; Das, Saumya (Indian Journal of Pharmaceutical Education and Research, 2018)
Aim: To evaluate the efficacy of a polyherbal formulation in alleviating urolithiasis induced by ethylene glycol in a rat model and to assess its effects on biochemical and histopathological parameters. Background: Urolithiasis is a condition characterized by the formation of stones in the urinary tract, often leading to significant health issues. This study investigates the anti-urolithiatic effects of a polyherbal formulation containing Aegle marmelos and Saraca asoca in albino Wistar rats. To investigate the anti-urolithiatic effects of a polyherbal formulation containing Aegle marmelos and Saraca asoca in albino Wistar rats. Materials and Methods: 36 albino Wistar rats were divided into six groups. Groups II, III, IV, V, and VI received drinking water containing 0.75% Ethylene Glycol (EG) to induce urolithiasis, while Group I served as the negative control. Groups IV and V were administered methanolic extracts of Saraca asoca and Aegle marmelos at a dose of 400 mg/kg body weight, while Group VI received the polyherbal formulation at the same dosage. After 28 days, various parameters, including urine volume, urinary oxalate and calcium levels, serum biochemical markers (blood urea, creatinine, uric acid), and histopathological changes in renal tissues, were assessed. Results: The positive control group exhibited significant decreases in urine volume, increases in urinary oxalate and calcium levels, and notable calcium oxalate deposits in the kidneys compared to the negative control group. Serum analysis indicated elevated levels of blood urea, creatinine, and uric acid in the urolithiasis control group. Conversely, treatment with the polyherbal formulation significantly reversed these biochemical alterations and reduced calcium oxalate deposits. Histopathological evaluations revealed reduced tissue damage and inflammation in the treatment groups compared to the control group. Conclusion: The polyherbal formulation demonstrated significant anti-urolithiatic effects in the rat model, reversing biochemical changes and alleviating kidney damage associated with urolithiasis. Further studies are warranted to explore the underlying mechanisms and potential clinical applications of this formulation.
Keywords: Urolihiasis; Urinary parameters; Serum parameters; Ethylene glycol; Aegle marmeos; Saraca asoca